Does science dissemination have a gender? Analysis of the articles published in The Conversation on Covid-19 - Eizmendi-Iraola, Maider; Peña-Fernández, Simón (TECHNO REVIEW. International Technology, Science and Society Review /Revista Internacional de Tecnología, Ciencia y Sociedad, 2023)
This article analyzes the articles published on Covid-19 in the Spanish version of The Conversation from a gender perspective through a quantitative and qualitative analysis of 306 texts published over a year. The results indicate a greater presence of men in the first moments of the health emergency, while female scientists have only had a greater presence in social issues. Likewise, the texts signed by women have obtained less interaction from the audiences and a higher proportion of negative responses.